Monetary Theories of the Rate of Interest: A Dynamic Analysis - Smith, Warren L. (The Review of Economics and Statistics, 1958)
DESPITE extensive controversy and discussion,1 the subject of monetary interest theory still seems to involve a considerable residue of confusion and uncertainty. While the writer does not pretend to be able to unsnarl all the tangled threads of this complex subject, it is hoped that the analysis presented here will serve three somewhat interrelated purposes: (i) to clarify the relation between the Keynesian liquidity preference theory and the loanable funds theory espoused by Robertson, Haberler, and others; (2) to produce a clearer understanding of the relation between stock and flow analysis in monetary theory; and (3) to develop an important distinction between (a) the determination of the rate of interest in a short period when the level of income is not in equilibrium, and (b) the forces that explain the change that occurs in the rate of interest during a longer period as the level of income moves from one equilibrium position to another.